A common transnational agenda? Communication network and discourse of political-Salafists on Twitter. Issue 2 (3rd April 2018) - Ranko, Annette; Nedza, Justyna; Röhl, Nikolai
Abstract: Employing social network analysis, this article investigates the transnational communication network and discourse of political -Salafists on social media. It examines whether political -Salafists across the MENA region have a common sociopolitical and geopolitical agenda, and whether – given the recent shift of some political -Salafists towards violence – their discourse and communication network can still be distinguished from that of the jihadists . The analysis finds that political -Salafists do not share a common agenda but that their discourse and communication network display three transnational gravity centres: a revisionist, a status quo-oriented and an ostracized pro-Sisi gravity centre. Only the revisionist gravity centre advocates violence. Its discourse, however, remains clearly set apart from that of the jihadists .